Non-Communicable Disease Screening Services for Teachers and Employees in the Senior High School (SMA) 3 Jayapura, Papua Province - Sitanggang, Prysta Aderlia; Setyarini, Kaida Irma; Labobar, Maryam Kathrien; Rumboirusi, Ricky Lazarus; Purnamasari, Try; Liufeto, Koherista G (Jurnal Pengabdian Masyarakat Bestari, 2024)
Non-communicable diseases (NCDs) are diseases that are caused by various factors and are not transmitted from individual to individual. Deaths caused by non-communicable diseases 35% are due to heart and blood vessel diseases, 12% by cancer, 6% by chronic respiratory diseases, 6% due to diabetes, and 15% due to other NCDs. Early detection through glucose, cholesterol & uric acid checks can prevent heart disease & diabetes. The target population in this community service is teachers and high school employees aged 25 – 60 years. The results of the examination showed that female teachers were more than male teachers. The age < 40 is more than teachers and employees aged >40 years. Patients with Hypercholesterolemia totaled 25 people (59%), indicating that high cholesterol was experienced by many teachers and employees at SMA N 3 Jayapura. Hypercholesterolemia can trigger the formation of atherosclerosis which causes blockages in the endothelium of blood vessels.